The Role of Trust Toward Continuance Usage Intention: of Mobile payment with Gender as Moderation - Laurence, Sontya; Candiwan (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The growth of financial technology is filled by digital wallet competition in the industry, one of the most known digital payment in Indonesia is OVO. Even so, the obstacles that OVO has can make users switch to another mobile payment provider. This research aims to analyze the impact on continuance usage intention by customers’ trust, and examine factors that influence trust in terms of gender moderation, the theories developed in this study are Innovation Diffusion Theory and Trust Building Framework. The method used to process data in this study are SEM and PLS. The findings of this research state that continuance usage intention is positively influenced by trust. Trust is significantly influenced by reputation, followed by customization, security, and mobility.